News of LGBT on online media in 2020: endless stigma - Listiorini, Dina; Vidiadari, Irene Santika (Jurnal Studi Komunikasi, 2022)
Mass media and its content on various platforms play a significant role in shaping knowledge in society, including the knowledge about sexuality. This article discusses news on LGBT on four Indonesian online media—Viva.co.id, Republika.co.id, Tempo.co.id, and Detik.com—by conducting quantitative content analysis. The result shows that the news on LGBT in 2020 centred on three main issues: the ban on gay individuals joining the army/police, the male rape case committed by Reynhard Sinaga, and male same-sex sexual intercourse in Wisma Atlet. The news structure on LGBT does not pay attention to the information depth, as indicated by the lack of paragraph numbers in the news and the lack of 5W+1H construction. In addition, the coverage is often one-sided, making it unbalanced. Eventually, the construct about LGBT becomes biased.